Temulawak (Curcuma xanthorrhizaRoxb.) belongs to the family Zingiberaceae, has been empirically used as herbal medicines. The research was aimed to evaluate three promising lines of Temulawak based on their high bioactive contents (xanthorrhizol and curcuminoid) and its in vitro bioactivity (antioxidant and toxicity), and to obtain information on agrobiophysic environmental condition which produced high bioactive compounds. The xanthorrhizol and curcuminoid contents were measured by HPLC. In vi - Waras Nurcholis; Edy Djauhari Purwakusumah; Mono Rahardjo; Latifah K. Darusman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
Temulawak (Curcuma xanthorrhizaRoxb.) belongs to the family Zingiberaceae, has been empirically used as herbal medicines. The research was aimed to evaluate three promising lines of Temulawak based on their high bioactive contents (xanthorrhizol and curcuminoid) and its in vitro bioactivity (antioxidant and toxicity), and to obtain information on agrobiophysic environmental condition which produced high bioactive compounds. The xanthorrhizol and curcuminoid contents were measured by HPLC. In vitro antioxidant and toxicity were determined by DPPH (1,1-diphenyl-2-picryl-hydrazyl) method and BSLT (Brine Shrimp Lethality Test). The result showed that promising line A produced the highest yield of bioactive and bioactivity, i.e. 0.157 and 0.056 g plant-1of xanthorrizol and curcuminoid respectively. The IC50 of antioxidant activity was 65.09 mg L-1and LC50of toxicity was 69.05 mg L-1. In this study, Cipenjo had the best temulawak performance than two other locations. According to the agrobiophysic parameters, Cipenjo environmental condition was suitable for temulawak cultivation with temperature 28-34 ºC, rainfall ± 223.97 mm year-1 and sandy clay soil. Keywords: antioxidant, curcuminoid, promising lines, temulawak, xanthorrhizol